Comparative study of laparoscopic Nissen fundoplication versus Hill-Snow procedure for the treatment of gastroesophageal reflux disease in children: a single-blinded randomized controlled trial - Mostafa Ahmed Gad; Mohamad Mahmoud Qinawy; Osama Abdelazim; Sherif Nabhan Kaddah; Mohamed Magdy Elbarbary; Mahmoud Asem Elfiky (SpringerOpen, 2023)
Abstract Background Gastroesophageal reflux disease (GERD) is a common condition in children. Complete fundoplication provides better reflux control but it results in more dysphagia and gas-bloat symptoms. Antireflux surgery without wrap has fewer adverse effects but a higher failure rate in controlling reflux. Until now, there is little evidence as to whether complete or partial fundoplication is the optimal procedure in this age group. Objective This study aimed to compare the safety and efficacy of laparoscopic Nissen fundoplication versus Hill-Snow procedure among children with GERD. Methods We conducted a randomized, single-blinded, comparative trial that included 40 children with a diagnosis of GERD, who were scheduled to undergo surgery. Children were randomly allocated to undergo laparoscopic Nissen fundoplication or Hill-Snow procedure. Results While the incidence of postoperative dysphagia was similar between both groups, the duration of dysphagia was significantly shorter in the Hill-Snow group. Likewise, the incidence of bloating was significantly lower in the Hill-Snow group than the Nissen group (0% versus 55%, respectively). We found three recurrent Hill-Snow cases versus two recurrent Nissen cases. The operative time was significantly longer in the Hill-Snow procedure (150 ± 52 min) than in the Nissen group (120 ± 48 min). Conclusions The Hill-Snow procedure is an effective alternative to Nissen fundoplication with no bloating and much less dysphagia, leading to faster recovery of ordinary eating patterns.